Chan-Chuang and resistance exercise for drug rehabilitation: a randomized controlled trial among Chinese male methamphetamine users - Li, Hansen; Wang, Chao; Huang, Xuemei; Xu, Lubing; Cao, Yang; Luo, Jiong; Zhang, Guodong (Frontiers in Public Health, 2023)
Objective To examine the health benefits of Chan-Chuang and resistance exercise. Methods We deployed an 8-week randomized controlled trial, in which 76 male methamphetamine users were allocated to control (n = 25), Chan-Chuang (n = 26), and residence exercise groups (n = 25). Our primary outcomes were drug craving, mental wellbeing, sleep quality, heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP). Our secondary outcomes were body mass index (BMI), vital capacity, grip strength, balance, and vertical jump. Results Chan-Chuang exercise resulted in reduced HR, DBP, and MAP, along with improvements in vital capacity, grip strength, and balance compared to the control group. Resistance exercise reduced SBP and MAP, and also improved vital capacity, grip strength, balance, and vertical jump. Conclusion These findings may support the role of Chan-Chuang and resistance exercise in maintaining the physical fitness of methamphetamine users at mandatory detention centers.